2019
DOI: 10.5604/01.3001.0013.2921
|View full text |Cite
|
Sign up to set email alerts
|

Results of Treatment of Type 3 Acromioclavicular Joint Dislocation with Three Methods

Abstract: Background. Rockwood Type III acromioclavicular joint injuries are treated both conservatively and surgically. There is still no consensus on an optimal fixation method. The aim of this study was to evaluate which of the surgical methods used in our Department produces the best outcomes in long-term follow-up. Material and methods. The study involved 27 patients. Wire cerclage was used in 12 patients, 11 patients were operated on by the Ladermann method, and a hook plate was used in 4 patients. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…With careful full‐text reading, 56 studies were excluded for the reasons shown in Figure 1. Finally, 31 articles were included in our study 24–54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With careful full‐text reading, 56 studies were excluded for the reasons shown in Figure 1. Finally, 31 articles were included in our study 24–54 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 31 articles were included in our study. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…After screening titles/abstracts for satisfying inclusion/exclusion criteria, 177 abstracts were further excluded, leaving 34 unique studies for full-text review. Finally, 14 studies that reported outcomes after the surgical management of acute Rockwood grade III acromioclavicular dislocations were included in this systematic review (Figure 1) [12,19,[26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Łazarski et al reported statistically significant improved CM scores in patients randomized to techniques in group 2 compared to the use of hook plates in group 1 (p = 0.04) [ 28 ]. Ye et al and Zhang et al also compared the use of hook plates (group 1) to a semitendinosus graft plus Endobuttons and the modified/common closed-loop double-button technique (group 2), respectively, both reporting generally better functional outcomes in patients who had the group 2 procedures [ 34 , 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Fakat aynı çalışmada bu üç yöntemin yaşam kalitesi açısından benzer olduğu belirtilmiştir. [12] Yapılan bir çalışmada; akromiyoklaviküler eklem çıkıkları için endo buton uygulanan hastaların, kanca plak uygulanan hastalara göre, erken dönem sonuçlarının daha iyi olduğu ancak bir yıllık takip sonunda, sonuçlarının benzer olduğu bildirilmiştir. [13] Rockwood tip III akromiyoklaviküler eklem çıkıklarında, korakoklaviküler ligaman tamiri yapmadan kanca plak uygulanması iyi bir uygulama olarak bildirilmiştir.…”
Section: Discussionunclassified